Pseudocyst in Neck: A Case Report on Rare Complication of Ventriculoperitoneal Shunt - Nitin, B.; Gupta, Manish; Singh, Anshul (Case Reports in Otolaryngology, 2021)
Introduction. Ventriculoperitoneal shunt is a common neurosurgical procedure, for the definitive management of hydrocephalus. Shunt failures may occur due to various causes but are usually due to infections in adults and catheter occlusion in the paediatric population. Case Report. The 13-year-old girl presented with a right lateral neck swelling. In detailed history, she was found to be an old case of ventriculoperitoneal shunt. The clinical examination and radiological investigation revealed proximal dislodgment of the stent from the cranium, causing persistent cerebrospinal fluid (CSF) leak and pseudocyst formation in the neck. Conclusion. The case highlights CSF pseudocyst formation as a rare differential for lateral neck swellings.